The application of rock phosphate increases the growth and yield of rice on acid sulphate soil of South Kalimantan, Indonesia - Suriyanti Ahmad; Sri Nuryani Hidayah Utami; Azwar Ma'as; Wahida Annisa Yusuf; Husnain Husnain (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
A swampland has considerable potential in agriculture. This land has high soil acidity level, and high iron content. Therefore, the application of ameliorant to acid sulfate soil is essential to improve the soil and make it more suitable for rice cultivation. This study aimed to know the effects of phosphorus (P) from Moroccan Rock Phosphate (MRP) and fertilization on swamp rice (Oryza sativa L.). The experiment was conducted at the experimental location of Indonesian Swampland Agricultural Research Institute (ISARI), Puntik Village, Barito Kuala District, South Kalimantan and arranged in a randomized nested design consisting of 100 kg.ha-1 TSP (Control), 750 kg.ha-1, 1,000 kg.ha-1, and 1,250 kg.ha-1 Moroccan rock phosphate with four replications in each treatment. The yield component of grain increased significantly at 3.77 ton.ha-1. The highest of grain yield was obtained in the application of 1,000 kg.ha-1 MRP. Meanwhile, significant positive correlation was observed between plant height and the number of spikelets per panicle. The application of phosphate fertilizer can increase soil pH, which affects the growth and yield of rice plants such as plant height and yield.